2020
DOI: 10.1111/1753-0407.13042
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic and other nonglycemic factors can predict large‐for‐gestational‐age infants in diet‐managed gestational diabetes mellitus: A retrospective cohort study

Abstract: BackgroundGestational diabetes mellitus (GDM) is one of the most common complications of pregnancy. Left untreated or poorly controlled, GDM results in adverse infant outcomes such as large for gestational age (LGA). This study aims to identify nonglycemic maternal and fetal factors predictive of LGA outcomes in pregnancies complicated by diet‐managed GDM.MethodsThis was a retrospective cohort study of singleton pregnancies complicated by diet‐managed GDM from 2004 to 2015. Multiple logistic regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…In pregnancies with GDM it has been reported that the AC is a more accurate predictor of macrosomia than the EFW; 2,13,20,29 however, our study showed similar associations (unadjusted OR F I G U R E 1 (A) Fetal abdominal circumference percentile distribution for women with gestational and type 2 diabetes. (B) Estimated fetal weight percentile distribution for women with gestational and type 2 diabetes.…”
Section: Mean (Sd)supporting
confidence: 65%
See 1 more Smart Citation
“…In pregnancies with GDM it has been reported that the AC is a more accurate predictor of macrosomia than the EFW; 2,13,20,29 however, our study showed similar associations (unadjusted OR F I G U R E 1 (A) Fetal abdominal circumference percentile distribution for women with gestational and type 2 diabetes. (B) Estimated fetal weight percentile distribution for women with gestational and type 2 diabetes.…”
Section: Mean (Sd)supporting
confidence: 65%
“…Hyperglycaemia in pregnancy is increasingly common 1 and poses significant risks to the neonate, including both excessive and restricted growth, neonatal hypoglycaemia, shoulder dystocia, intensive care admission, acidosis, jaundice, respiratory distress, prematurity, as well as long-term metabolic consequences. [2][3][4] Identifying infants antenatally who may be large for gestational age (LGA) or small for gestational age (SGA) can reduce neonatal morbidity and mortality. [5][6][7] Studies of antenatal ultrasound have described accuracy in predicting birth weight; 8,9 however, few have quantified the association between growth parameters and other markers of neonatal morbidity and mortality, 6 particularly in pregnancies complicated by hyperglycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that all fetal biometric growth parameters were significantly higher in women with gestational diabetes than in women with normal blood glucose status, and these results are supported with the findings of other studies as well [ 36 ]. Both GDM and maternal pre-pregnancy obesity might have an individual as well as cumulative effects on fetal as well as on neonatal anthropometric parameters [ 37 , 38 ]. Additionally, in the study published by Chee et al fetal AC was identified as a predictor of LGA.…”
Section: Discussionmentioning
confidence: 99%
“…We have also found strong positive correlation between AC and GDM, leading us to believe that AC might be a potent parameter in early assessment of both GDM and LGA. Therefore, this parameter could be used also as a potential marker for the fetal monitoring and surveillance during pregnancy [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies with a fetal biometry ultra-sound measure near the time of GDM diagnosis, six of the eight studies found that larger fetal abdominal [81][82][83][84][85] or biparietal circumference 22 was positively associated with greater neonatal size (birthweight, LGA, macrosomia).…”
Section: Fetal Biometrymentioning
confidence: 99%